Manajemen Dan Akuntabilitas Sekolah - Zulkifli Umar, Budi Safatul Anam, Tarmizi Gadeng, Hendri mauliansyah, Rahma Nurzianti, Rusnaidi (JKA, 2024)
The future of a country depends heavily on education, with school accountability and school management as key elements. School management involves planning, organizing, implementing, and supervising educational activities, focusing on the effective management of educational resources and processes, including school leadership, staff management, and community engagement. School accountability is the key to high quality education, including stakeholder responsibility, transparency of fund management, student learning outcomes evaluation, and teacher performance evaluation. Accounting also supports accurate financial reporting, creates an optimal learning environment, and improves resource management transparency. The International Community Engagement Program at Hotel Linge Land, Central Aceh, focuses on location surveys, coordination with relevant agencies, deposits of members of the PKM, fundraising, and other technical measures. The PKM International seminar was attended by various parties, including the head of school, representatives of the Education and Development Service of Central Aceh, lecturers, and students. Implementation of the PKM involved comprehensive surveys to identify the needs of the community, fund-raising strategies involving the lecturer, expert meeting forums, field visits, and preparation of effective seminars. Evaluation of PKM activities involves the head of the school and related agencies to evaluate the success of the project, positive impact on the community, local involvement in sustainability, and community participation.